Comparative efficacy and safety of glucose‐lowering drugs as adjunctive therapy for adults with type 1 diabetes: A systematic review and network meta‐analysis. Issue 3 (6th January 2021) - Avgerinos, Ioannis; Manolopoulos, Apostolos; Michailidis, Theodoros; Kitsios, Konstantinos; Liakos, Aris; Karagiannis, Thomas; Dimitrakopoulos, Konstantinos; Matthews, David R.; Tsapas, Apostolos; Bekiari, Eleni
Abstract: Aim: To assess the efficacy and safety of glucose‐lowering drugs used as an adjunct to insulin therapy in adults with type 1 diabetes. Methods: We searched Medline, Embase and the Cochrane Central Register of Controlled Trials up to 24 January 2020 for randomized controlled trials. Our primary outcome was change in HbA1c. We additionally assessed eight efficacy and six safety secondary endpoints. We performed random effects frequentist network meta‐analysis to estimate mean differences (MDs) and odds ratios (ORs), alongside 95% confidence intervals (CIs). We assessed risk of bias and evaluated confidence in the evidence for the primary outcome. Results: We included 58 trials comprising 13 216 participants. Overall, sodium‐glucose co‐transporter (SGLT) inhibitors, liraglutide, glibenclamide, acarbose and metformin reduced HbA1c compared with placebo (MDs ranging from −0.46% [95% CI −0.64% to −0.29%] for empagliflozin to −0.20% [−0.35% to −0.06%] for metformin). SGLT inhibitors, exenatide daily, liraglutide and metformin reduced body weight and total daily insulin dose, while liraglutide and SGLT inhibitors reduced blood pressure. Diabetic ketoacidosis and genital infections were more frequent with SGLT inhibitors, while exenatide, liraglutide, pramlintide and metformin increased the incidence of nausea. No drug increased the incidence of severe hypoglycaemia. Confidence in evidence was mainly moderate to very low. Conclusions: Specific drugs may improve glycaemic control and reduce body weight, blood pressure and total daily insulin dose in patients with type 1 diabetes. However, low quality of evidence and an increased risk of diabetic ketoacidosis, genital infections or gastrointestinal adverse events should be taken into consideration by healthcare providers and patients. Future long‐term trials are needed to clarify their benefit‐to‐risk profile and elucidate their role in clinical practice.